2013
DOI: 10.1021/bc3006122
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Site-Specific PEGylation on the Conformational Stability and Folding Rate of the Pin WW Domain Depends Strongly on PEG Oligomer Length

Abstract: Protein PEGylation is an effective method for reducing the proteolytic susceptibility, aggregation propensity, and immunogenicity of protein drugs. These pharmacokinetic challenges are fundamentally related to protein conformational stability, and become much worse for proteins that populate the unfolded state under ambient conditions. If PEGylation consistently led to increased conformational stability, its beneficial pharmacokinetic effects could be extended and enhanced. However, the impact of PEGylation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 65 publications
2
65
0
Order By: Relevance
“…At its most advanced stage, conjugate research applies the tools of medicinal chemistry by incorporating insights from structure–function studies into the design of the molecule. A study 64 of the site-specific pegylated WW domain of the human protein peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (PIN1) 65 showed that conformational stability depends on the molecular mass of PEG; longer oligomers increased the folding rate and reduced the rate of protein unfolding.…”
Section: Injectable Modified Peptides and Proteinsmentioning
confidence: 99%
“…At its most advanced stage, conjugate research applies the tools of medicinal chemistry by incorporating insights from structure–function studies into the design of the molecule. A study 64 of the site-specific pegylated WW domain of the human protein peptidyl-prolyl cis-trans isomerase NIMA-interacting 1 (PIN1) 65 showed that conformational stability depends on the molecular mass of PEG; longer oligomers increased the folding rate and reduced the rate of protein unfolding.…”
Section: Injectable Modified Peptides and Proteinsmentioning
confidence: 99%
“…We recently showed that attaching a short PEG (comprising four ethylene oxide units) to a single Asn side chain at position 19 in the WW domain of the human protein Pin 1 increases WW conformational stability by −0.70 ± 0.04 kcal mol −1 due to accelerated folding and slowed unfolding [57] (see figure 2). Shorter PEG chains impart less stability to WW than the four-unit PEG, whereas longer PEG chains provide similar stability.…”
Section: How Peg Enhances Protein Conformational Stabilitymentioning
confidence: 99%
“…The difference in stability between 1-nbp and 1p cannot be attributed solely to the fact that 1-nbp contains four more ethylene oxide units than 1p : branched 1-nbp is also more stable than a previously characterized derivative of 1p that has eight ethylene oxide units instead of four. 25 This observation highlights the possibility that branched PEGs may be more effective at increasing protein stability than linear PEGs of similar molecular weight.…”
Section: Resultsmentioning
confidence: 90%